The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1474904116654917
|View full text |Cite
|
Sign up to set email alerts
|

Information We Collect: Surveillance and Privacy in the Implementation of Google Apps for Education

Abstract: The aim of this study is to show how Google's business model is concealed within Google Apps for Education (GAFE) as well as how such a bundle is perceived within one educational organisation, consisting of approximately 30 schools. The study consists of two parts: 1) a rhetorical analysis of Google policy documents and 2) an interview study in a Swedish educational organisation. By making an implicit demarcation between the two concepts (your) 'data' and (collected) 'information' Google can disguise the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 36 publications
3
55
0
10
Order By: Relevance
“…While ethical design and use can encompass many components, we focused on the transparency and truthfulness of Google by turning to their own words and standards. Lindh and Nolin ( 2016 ) conducted a rhetorical analysis of Google’s policy documents relating to Google Apps for Education (GAFE; now Google Workspace for Education) and concluded that the company’s primary aim was to “ disguise the business model and to persuade the reader to understand Google as a free public service, divorced from marketplace contexts and concerns” (p. 650). The company often emphasized the free services they offer on the front-end, but obfuscated their back-end business model of extracting users’ personal data to profit from targeted advertising.…”
Section: A Technoethical Approachmentioning
confidence: 99%
“…While ethical design and use can encompass many components, we focused on the transparency and truthfulness of Google by turning to their own words and standards. Lindh and Nolin ( 2016 ) conducted a rhetorical analysis of Google’s policy documents relating to Google Apps for Education (GAFE; now Google Workspace for Education) and concluded that the company’s primary aim was to “ disguise the business model and to persuade the reader to understand Google as a free public service, divorced from marketplace contexts and concerns” (p. 650). The company often emphasized the free services they offer on the front-end, but obfuscated their back-end business model of extracting users’ personal data to profit from targeted advertising.…”
Section: A Technoethical Approachmentioning
confidence: 99%
“…Security, privacy and data protection issues are therefore of particular concern given the wealth of personal data that may exist on or be generated from personal devices (Miller, Voas, and Hurlburt 2012). There are also a number of ethical issues to consider concerning the use of profit-making online tools (Purvis, Rodger, and Beckingham 2016), which can collect and disseminate personal data for advertising firms to exploit (Lindh and Nolin 2016), or who may share or sell users data or content (Kelly et al 2018b).…”
Section: (Page Number Not For Citation Purpose)mentioning
confidence: 99%
“…Les chercheurs critiques explorent également le rôle des technologies dans l'automatisation de l'activité scolaire, depuis les systèmes d' évaluation automatisée de tests et d' essais jusqu'aux systèmes d'apprentissage personnalisé qui régulent et individualisent le parcours de chaque étudiant, sans intervention de l' enseignant (Lundie, 2016;Thompson, 2016). Des questions du même ordre se posent au sujet de la surveillance et du contrôle via les technologies (Lindh et Nolin, 2016;Nemorin, 2017). Bien que ces « innovations » soient officiellement justifiées en termes d'efficacité accrue et de rationalisation, les études critiques permettent d' ouvrir sur des explications alternatives possibles dans lesquelles les technologies sont utilisées pour maintenir l' exploitation, la performance et l'aliénation.…”
Section: L'éducation Et La Nature Changeante Du « Travail » à L'ère Dunclassified